Radiation ultraviolet-c for bacterial disinfection (total and thermotolerant coliforms) in the water treatment - Rossel Bernedo, Luis Jhordan (2020)
The study aimed to evaluate the presence of bacteria (total and thermotolerant coliforms) in the treatment of water using Class C Ultraviolet Radiation (UV-C), the research was carried out in the Quality Control Laboratory of the Treatment Plant  of Potable Water of the EPS, EMSA Puno, because current regulations require that total and thermotolerant coliform readings in drinking water should be 0 CFU / 100 ml, with UV-C radiation being an alternative for the decrease in  Chlorine use.  For what was experimented with a dose of 0,00176 W/cm2/s of UV-C radiation with a dominant wavelength of 254 nm, the experimental water samples were subjected to 1, 2, 3, and 4 seconds of exposure to the mentioned radiation.  For the determination of the bacterial presence in water (total and thermotolerant coliforms), the Membrane Filter methodology was chosen, the results obtained for the total coliform count were readings on average of 200, 165, 59 and 0 CFU/100 ml  and for the count of thermotolerant coliforms average readings of 4, 3, 1 and 0 CFU/100 ml.  Concluding that, for the total inactivation of the total coliforms and thermotolerant coliforms present in the water samples, a minimum time of 4 s of exposure to UV-C radiation was required.